Pengaruh Likuiditas, Perputaran Modal Kerja, dan Leverage Terhadap Profitabilitas Perusahaan BUMN Non-Perbankan Yang Terdaftar di BEI - Fransiska, Benna; Nilwan, Afrizal (Jurnal EMT KITA, 2023)
The main objective of this research is to study the impact of Leverage (X1), working capital turnover (X2) and liquidity (X3) on profitability (Y) of non-bank public enterprises. products listed on the Indonesia Stock Exchange in 2019 - Period 2021. The research method used is quantitative, with subjects including non-bank public companies that have become public companies from 2019 to 2021. Sampling was carried out using the purposive sampling method, which selected 13 non-bank public enterprises as the research sample. Data analysis was performed using a multiple linear regression model. The results of this study show that liquidity (X1) and working capital turnover (X2) have a significant positive impact on profitability, while Leverage (X3) has a significant negative impact on profitability. These results provide valuable information to stakeholders of non-banking public enterprises in managing their financial aspects to increase profitability and corporate performance.